Pamela J. Olubunmi Smith’s Translation Style in The Freedom Fight and Treasury of Childhood Memories - Tolulope Ibikunle (Yoruba Studies Review, 2022)
The steady but relentless globalization of the world makes translation highly pertinent to the understanding of different endeavors and spheres, from education and the economy to politics and religion. Thus, translation as a conduit for the transmission of knowledge protects and promotes tradition, culture and literature in our contemporary world. Consequently, translators are of utmost importance to the world at large and their immediate society in particular. Literary works exhibit diverse linguistic components, coupled with social, religious and cultural aspects of human existence, hence translation of literary works could be regarded as one of the main communicative approaches across cultures. Translating literary works, thus, constitutes many problems for the translator who is expected to be both bilingual/multilingual and bicultural/multicultural. Therefore, this essay will examine the roles and challenges of cultural and textual translation in the context of African society through the contribution and dexterity of Pamela J. Olúbùnmi Smith. Since the translation of literary work is also a form of adaptation and not pure language translation, attention will be placed on Smith's artistic prowess and translation techniques by analyzing two of her translated works. While reflecting on salient challenges of translation and the impacts of translating literary works from Pamela J. Olubunmi Smith's perspective, the essay aims to address some of the ways she gets to grips with the challenges to promote the Yorùbá language, culture, religion and tradition, as a translator. The essay concludes by advocating for better circulation, promotion and expansion of the cultural, philosophical, religious, political and social ideas of Africans through translations of literary works written in English, French and other languages into African languages and those written in African languages into English, French and other languages.